The Analysis of Community Satisfaction Index at the Population and Civil Registration Service (Disdukcapil) of Central Bengkulu Regency - Anita Sari;; Sulisti Afriani; Nenden Restu Hidayah (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Generally, public service problems can be seen from the low skills of the apparatus and the lack of work equipment, causing uncertain and imprecise service schedules and impacting community satisfaction in public services. Community Satisfaction Index (IKM) is one of the methods used to determine the quality of public services through public perceptions. This study aims to determine the index of community satisfaction with health services at the Population and Civil Registration Service (Disdukcapil) of Central Bengkulu Regency. The analytical method used is the Community Satisfaction Index (IKM) with 9 service elements in accordance with Permenpan and Bureaucratic Reform No. 14 of 2017. Samples in this study were 226 respondents. The results showed that the service satisfaction of the Population and Civil Registration Service (Disdukcapil) of Central Bengkulu Regency was good, this can be seen from the high IKM score of 84.398 which is included in the service quality category is "B", which means service quality is already good. From the nine elements of service used. Fees/tariffs are a service element with the highest index value with an IKM value of 3.91 with an IKM conversion value of 97.68 in the very good performance category. While the element with the lowest index value is implementing competency with an IKM value of 3.14 and an IKM conversion value of 78.43 in the good category..